Persepsi masyarakat luar bandar di Daerah Kota Samarahan terhadap masalah sosial di kalangan remaja - Ruzitha, Binti Mustafa (Universiti Malaysia Sarawak, (UNIMAS), 1997)
This research was undertaken to investigate the perception of society whom living at Kota Samarahan District towards juvenile delinquents. The study also aim to identify the relationship between society' education level and their perception towards social problems among the juveniles. A total of 120 adults were selected randomly. Data were collected using questionnaire but only 100 questionnaires were jkendy complet4 and returned back to researcher successfully. Data were analysed using SPSS (statistical package for Social sciences) computer programmes especially frequency analysis and chisquare. From the findings, it showed that generally the society at Kota Samarahan were aware and concern towards social problems that always occur among the juveniles. The results showed that the gruelling problem, school's truancy and shifting the glue became the dominant of deviant behaviour that done by youths at Kota Samarahan. Besides that, the research finding also showed that Kota Samarahan's society have been practised the authoritarian attitude in disciplinary their child especially the youths. There also showed that the educational level not associated significantly with society's perception toward social problem among the juveniles.